Role of pectin in maintaining the physicochemical, textural, rheological, and organoleptic properties of model quark cheese spreads during simulated vibrations and storage - Gryger, T; Stěnička, M; Vincová, A; Lorencová, E; Šantová, K; Salek, R N (International journal of biological macromolecules, 2025)
This study examined the effects of incorporating pectin and applying simulated mechanical vibrations on the physicochemical, textural, rheological, and organoleptic attributes of Quark cheese spreads (QCS) over a storage period of 30 days (6 ± 2 °C). The QCS model samples were prepared with pectin concentrations of 0.50, 0.75, and 1.00 % w/w and subjected to vibrational loading to simulate transportation conditions. Key physicochemical parameters, including dry matter (DM), fat and protein content, water activity, and pH, were measured on day 2 and 30 after preparation. Vibrations significantly affected the hardness, spreadability, and water holding capacity (WHC) of the samples, with increased pectin concentrations leading to greater hardness and greater force required for spreading, particularly in non-vibrated samples. Rheological analysis revealed that vibrational loading reduced viscoelastic moduli (G' and G"), with the elastic character prevailing in all samples (tan δ < 1). Sensory evaluation demonstrated a minimal influence of vibrations on assessor perception, except at higher pectin concentrations. It could be concluded that vibrations negatively affected the textural and viscoelastic properties and WHC of the QCS model products. To avoid the problems mentioned above, the data presented in this study may be useful in developing formulations and transportation systems for QCS products.
Keywords: Cheese; Humans; reologie; Sensory properties; viskozita; Pectins; Viscosity; lidé; Rheology; Food Storage; vibrace; sýr; Chemical Phenomena; Vibration; Vibrational loading; Mechanical properties; voda; Hydrogen-Ion Concentration; chemické jevy; Water; High methoxyl pectin; Quark cheese spread; koncentrace vodíkových iontů; skladování potravin; pektiny